Influence of digital health on public health protection against the COVID-19 panademic in Algeria - Bouriche, Ahmed; Bouriche, Sihem (Journal of Education, Health and Sport, 2022)
Covid-19, many challenges were faced by the people. Lacking of medical health facilities were top listed among these challenges. As a result of these issues, the medical system is paying more attention to digital Health. The purpose of this study was to examine the influence of digital health on public health protection against the COVID-19 pandemic via public health awareness and public health behavioural changes as mediating factors in Algeria. Population of the study was comprised of Algerian doctors and nurses. Five hundred and twenty two (522) respondents were selected as sample by using available sampling technique. For the collection of data a self-made questionnaire was developed and used for the collection of data. The collected data were analysed by using PLS-Smart program. Based on analysis, the researcher concluded that adoption of digital health can have a positive impact on public health behavioural changes and COVID-19 protection.